PERANCANGAN KEY PERFORMANCE INDICATOR (KPI) INSTALASI RADIOLOGI MENGGUNAKAN METODE BALANCED SCORECARD DI RS BAPTIS BATU - Verliana Floyani Uly (CHMK HEALTH JOURNAL, 2018)
Background : Radiology Installation in Baptis Batu Hospital is one of five revenue centers. As the center of production costs, unit performance measurement is necessary in Radiology Installation so that the vision and strategy of the hospital can be translated well, measurable and appropriate. One way of measuring the performance of Radiology Installation is with Key Performance Indicator (KPI). Balanced Scorecard is a management system capable of helping organizations to sharpen their vision and strategy, translating into action. Balanced Scorecard method becomes an option in overcoming the problem of unit indicator in Baptis Hospital because this method is very effective to determine hospital performance accurately and comprehensively. The purpose of this research is to develop Key Performance Indicator using Balance Scorecard. Method: The research method used is descriptive qualitative approach based on primary data through observation and interview and secondary data in the form of monthly report and annual report. Result: The result of this research is Key Performance Indicator (KPI) of Radiology Installation at Baptis Batu Hospital. Keywords : Balanced scorecard (BSC), Key Performance Indicator (KPI)